The Role Of Teacher Communication In Forming Students' Discipline Character At Madrasah Ibtidaiyah Amanah Kandis District - Melani, Uci; Irasari, Irasari (EL-EMIR Institute, 2024)
This study aims to explore the role of teacher communication in the formation of the disciplinary character of students at Madrasah Ibtidaiyah (MI) Amanah, Kandis District. This research uses a qualitative approach with the case study method. Data was collected through class observation, interviews with teachers and students, and analysis of related documents. The results of the study show that teacher-student communication acts as an important link in fostering the disciplinary character of students. Teachers who are able to communicate well can form harmonious and respectful relationships with students, so students feel more motivated to maintain self-discipline. In addition, empathetic and responsive teacher communication helps students express feelings, thoughts, and problems they face. so that it can help overcome obstacles in the formation of disciplinary character. Teachers also act as role models for students in demonstrating expected disciplinary behavior. However, this study also found that challenges in teacher-student communication at MI Amanah Kandis District, such as the diverse social and cultural environment of students, as well as the large number of students in one class , can affect the effectiveness of communication and the formation of disciplinary character.